Results of the Italian infection-Carbapenem Resistance Evaluation Surveillance Trial (iCREST-IT): activity of ceftazidime/avibactam against Enterobacterales isolated from urine. (20th January 2020) - Giani, Tommaso; Antonelli, Alberto; Sennati, Samanta; Di Pilato, Vincenzo; Chiarelli, Adriana; Cannatelli, Antonio; Gatsch, Christopher; Luzzaro, Francesco; Spanu, Teresa; Stefani, Stefania; Rossolini, Gian Maria
Abstract: Objectives: To assess the in vitro antibacterial activity of ceftazidime/avibactam against a recent Italian collection of carbapenem-resistant Enterobacterales (CRE) isolated from urine specimens. Methods: Consecutive Gram-negative isolates from urine specimens, collected from inpatients in five Italian hospitals during the period October 2016 to February 2017, were screened for CRE phenotype using chromogenic selective medium and identified using MALDI-TOF MS. Antimicrobial susceptibility testing was performed by reference broth microdilution (BMD) and, for ceftazidime/avibactam, also by Etest ® CZA. Results were interpreted according to the EUCAST breakpoints. All confirmed CRE were subjected to real-time PCR targeting bla KPC-type, bla VIM-type, bla NDM-type and bla OXA-48-type carbapenemase genes. Non-MBL-producing isolates resistant to ceftazidime/avibactam were subjected to WGS and their resistome and clonality were analysed. Results: Overall, 318 non-replicate presumptive CRE were collected following screening of 9405 isolates of Enterobacterales (3.4%) on chromogenic selective medium. Molecular analysis revealed that 216 isolates were positive for a carbapenemase gene (of which 92.1%, 2.8%, 1.4% and 1.4% were positive for bla KPC-type, bla OXA-48-type, bla NDM-type and bla VIM-type, respectively). Against the confirmed carbapenemase-producing Enterobacterales (CPE), ceftazidime/avibactam was the most active compound, followed by colistin (susceptibility rates 91.6% and 69.4%, respectively). Compared with BMD, Etest ® for ceftazidime/avibactam yielded consistent results (100% category agreement). All class B β-lactamase producers were resistant to ceftazidime/avibactam, while OXA-48 and KPC producers were susceptible, with the exception of seven KPC-producing isolates (4.2%). The latter exhibited an MIC of 16 to >32 mg/L, belonged to ST512, produced KPC-3 and showed alterations in the OmpK35 and Ompk36 porins. Conclusions: Ceftazidime/avibactam showed potent in vitro activity against a recent Italian collection of CPE from urine.